Characteristic of Five Subpopulation Leukocytes in Single-Cell Levels Based on Partial Principal Component Analysis Coupled with Raman Spectroscopy. Issue 12 (December 2020) - Li, Wenxue; Wang, Liu; Luo, Chuan; Zhu, Zhiqiang; Ji, Jianlong; Pang, Lin; Huang, Qing
Characteristics of five subpopulation leukocytes in single-cell levels based on partial principal component analysis coupled with Raman spectroscopy were proposed to recognize the biochemical features of five subpopulation leukocytes. Using wavelet transform, the reconstructed spectra of the low-frequency wavelet coefficients were used to perform multiple principal component analysis based on segmented spectral data wreathing cover at 720–800 cm –1, 840–994 cm –1, and 1010–1070 cm –1 wavenumbers, respectively. Our approach is promising since it enables to establish a better understanding of the underlying molecular difference between the subtypes of leukocytes in a label-free manner and to estimate the source of infection.